Evaluation of a Literacy Camp to Counteract Summer Learning Loss - Papi, Cathia; Desjardins, Guillaume; Kaboré, Tigawendé (Mesure et évaluation en éducation, 2023)
During the COVID-19 pandemic, the government of Quebec introduced a measure to fight summer learning loss referred to as the “summer slide”. As a result, since 2021, funding has been provided for organizing summer programs to support pupils’ learning during school vacations. This article focuses on the evaluation of a camp called Literacy Through Fun offered at a school service center. The aim of this article is to measure how likely such a program stems summer learning loss and promotes learning retention during the summer. A mixed methodology was used, combining a qualitative approach based on semi-structured interviews and a quantitative approach based on pre- and post-tests. The results of the study of this literacy camp are positive and significant, showing that participation in the camp enables pupils to maintain and even improve their literacy skills over the summer.